Application of an Agro-Waste for the Immobilization of Microbial Fructosyltransferase: A New Alternative for Fructooligosaccharide Production - Pereira, Richard S.; Vieira, Ana C.; Leite, Paula C.; Maestrelli, Sylma C.; Silva, Elda S.; Maiorano, Alfredo E.; Xavier, Michelle C.A.; Lopes, Melina S.; de Paula, Ariela V. [UNESP]; Morales, Sergio A.V.; Perna, Rafael F. (Sociedade Brasileira de Quimica (SBQ), 2025)
This work evaluated the use of corncob as a support for the immobilization of an extracellular fructosyltransferase (E.C. 2.4.1.9) from Aspergillus oryzae IPT-301, aiming at the synthesis of a stable biocatalyst for the production of fructooligosaccharides. The transfructosylation activity of the immobilized enzyme was maximized via experimental design. Additionally, the biochemical properties and stability of the immobilized enzyme, as well as the reaction kinetics, were determined. The enzyme immobilized on alkali-treated corncob showed the highest transfructosylation activity at 50 °C and pH 5.5. It also presented a wide pH stability and a half-life around 1.4 times greater than the soluble enzyme. Furthermore, the immobilized enzyme showed 53% of retention of catalytic activity in a second consecutive reaction cycle, showing the potential for reuse. These results suggest that alkali-treated corncob is a promising support material for the synthesis of heterogeneous biocatalysts aiming at fructooligosaccharide production, which can contribute to the valorization of this abundant agro-waste.
Keywords: corncob; fructooligosaccharides; fructosyltransferase; immobilized enzyme